Analisis Tax Review Atas Surat Pemberitahuan Tahunan CV. Prema Desain Tahun Pajak 2020 - Wijaya, I Wayan Kusuma; Kusumawati, Ni Putu Ayu (Hita Akuntansi dan Keuangan, 2025)
Finding the Tax Review Analysis of the Calculation of Annual Notification Letters for the Period of CV is the aim of this study. Design by Prema. Qualitative methods were employed to obtain data for the study through interviews and documentation. This study employed engineering triangulation as a data analysis method. Gathering data, condensing data, presenting data, and generating conclusions are the tasks involved in data analysis. The investigation's findings are CV. Prema Design has reported VAT and PPh Article 21 properly and correctly according to existing regulations. This is proven by the equalization of VAT in 2023 and PPh article 21 which does not cause a difference. Based on the profit/loss report of CV. Prema Design throughout the time frame of January 1, 2023, to December 31, 2023, it is evident that the computation of fiscal adjustments was accurate, either negative fiscal corrections or positive fiscal corrections”.